Awareness about preventive measures that reduce the risk of breast cancer among menopausal women - Chavda, Bhakti C.; Patel, Farheen S.; Ray, Manish M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Breast cancer is the most common malignant cancer and the second leading cause of cancer death in women. In 2020, there were 2.3 million women diagnosed with breast cancer and 6,85,000 deaths globally. Mortality due to breast cancer is found to be high in the developing countries because they seek medical attention at advanced stages due to lack of awareness and low socio-economic status. As there is no uniform education policy for breast cancer prevention and there is no acceptable strategy for breast cancer prevention throughout the nation, we thought to assess about awareness of preventive measures that reduce risk of breast cancer in menopausal women. Methods: For data collection, consent was taken from the participants and a questionnaire was given to them through Google form. Once the data was collected, descriptive data analysis was done on it. Results: This study found that 80.6% of women are aware of the term ‘breast cancer’ in general. Women are comparatively more aware about primary preventive measures than about secondary preventive measures. The study also found that some women have myths regarding risk factors and preventive measures of breast cancer. Conclusions: The study found that women are more aware about primary preventive measures than about secondary preventive measures. Also, some women have myths regarding risk factors and preventive measures of breast cancer.